Influence of Employee Discipline, Compensation and Employee Load on Employee Performance in PT. Tozy Sentosa in Surabaya - Indah Kusasih; Hermien Tridayanti (NAROTAMA UNIVERSITY, Indonesia, 2020)
This study aims to determine the effect of simultaneous and partial compensation and workload discipline on the performance of employees of PT. Tozy Santosa Surabaya. This research is a quantitative study. Population and sample based on the distribution of questionnaires to the performance of the employees of PT. Tozy Santosa Surabaya was taken as many as 40 respondents. Data collection techniques used interviews, observations and questionnaires. Data analysis used was reliability test, validity test, classic assumption test and multiple linear analysis test. The results of the study were simultaneous and partial discipline, compensation and workload significant effect on the performance of employees of PT. Tozy SantosaSurabaya because of the significance of <0.005.